Analisis Layanan Administrasi Kependudukan Berbasis Digital Melalui Aplikasi Pak Dalman (Pelayanan Administrasi Kependudukan Dalam Genggaman) di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Kendal Tahun 2024 - Rantika Alfiana Safitri; Neny Marlina (Journal of Politic and Government Studies, 2026)
The implementation of public services is currently faced with various changes and increasingly dynamic demands of society. One of the government's efforts to improve the quality of public services is through information technology-based innovation. The Population and Civil Registration Office of Kendal Regency, as the implementer of population administration services, has developed a digital-based service through the Pak Dalman application (Population Administration Services in Your Hand). This service aims to provide easier access to faster, more transparent, and free services for the public. The purpose of this study is to analyze the application of the concept of digitalization in population administration services through the Pak Dalman application. As well as to identify the impact of its use on improving the quality of public services in Kendal Regency, including aspects of transparency and accountability. This study uses a qualitative method with a descriptive approach. Data collection techniques are carried out through interviews, observation, and documentation. In-depth interviews were conducted with the Head of the Population Administration Information Management Division, Implementers in the Population Administration Information System Section, and community users of the Pak Dalman application. The collected data were analyzed using the theory of E-Government implementation and the theory of the impact of the use of information technology in improving the quality of public services to answer the formulation of the research problem. The results of the study indicate that the support indicator, the implementation of digitalization through the Pak Dalman application is not fully optimal, indicated by the lack of regulatory support for the application's implementation at the regional level and uneven socialization, so that some people still do not understand the mechanism of using the Pak Dalman application. In the capacity indicator, human resource readiness with the presence of competent officers, supported by an adequate budget and technological infrastructure in the form of servers, networks and security systems centralized at the Kendal Regency Communication and Informatics Office. In addition, the implementation of the Information Security Management System (ISMS) and the ISO 27001:2022 Standard, is an effort to maintain the security and protection of public data. In the value indicator, the Pak Dalman application is able to provide services that are easy, fast, free and can be accessed at any time, thereby increasing service efficiency. Overall, the use of the Pak Dalman application has a positive impact on the quality of public services, especially in increasing transparency through information disclosure and accountability through fast, accurate services, and the availability of accountable complaint channels. However, in the aspect of participation, community involvement is needed in the planning stage of digital service development, so that it is necessary to strengthen collaboration between the government and the community.